MULTI-OBJECTIVE SYNTHESIS OF CONFLICT-FREE AIRCRAFT TRAJECTORIES - Васильєв, Д. В. (Science-based technologies, 2014)
The problem of multi-objective synthesis of trajectories for aircraft conflict resolution is considered. The optimality criteria that characterize the efficiency of conflict resolution are regularity of flights, economy of flights and maneuvers complexity. Resolution of the potential conflict considered as the sequential multistage decision-making process in discrete time and the maneuvering aircraft considered as the discrete dynamic system. The method of sequential conflict-free space-time trajectories synthesis using multi-objective dynamic programming was developed. The functional equations of bottom-up and top-down multi-objective dynamic programming procedures for determining the set of Pareto-efficient estimations of conflict-flight trajectories are shown. The procedure for selection of the optimal trajectory from the set of Pareto-efficient based on method of criteria convolution is defined.